Global environmental commons: analytical and political challenges in building governance mechanisms - Brousseau, Éric (Oxford University Press, 2012)
This text provides an overview of global environmental governance and the effectiveness of different governance mechanisms. Bringing together a broad range of perspectives, it addresses key challenges in contemporary global governance of environmental change.
Keywords: Aufsatzsammlung; Umweltpolitik; Globalisierung